Estilos de vida saludable y conciencia ambiental en estudiantes del nivel primaria de una institución educativa del distrito de Pólvora, Tocache - Del Castillo Chávez, Dámaris (2023)
This research aimed to determine the relationship between healthy lifestyles and environmental awareness in fifth-grade students of an educational institution. The research type was basic, correlational, and non-experimental; the hypothetical-deductive method was employed, and a Likert scale questionnaire was administered to a sample of 30 fifth-grade students. For the analysis and interpretation of results, the Shapiro-Wilk statistic was used, given the sample size being less than 50, and the Spearman correlation statistic. The results demonstrated a contrast between the study variables, with a Spearman's Rho reaching the value of 0.717, categorizing it as a high correlation. In conclusion, it is affirmed that healthy lifestyles and environmental awareness are closely linked, as the students' decisions promoting personal health often coincide with positive actions for environmental care.